2013
DOI: 10.1007/s00508-013-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum persistent proteinuria after preeclampsia: a single-center experience

Abstract: Persistent proteinuria is the most important predictor of underlying renal disease after delivery. All patients with preeclampsia should be evaluated with respect to continuing proteinuria, persistent hematuria, or impaired renal functions after postpartum period and a percutaneous renal biopsy should be performed in those patients who have positive signs of underlying renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
19
1
1
Order By: Relevance
“…37 These women should be evaluated with respect to continuing proteinuria, persistent hematuria, or impaired renal function and a percutaneous renal biopsy should be performed in women who have positive signs of underlying renal disease. 30 Limitation of our study-We did not study the diagnosis-todelivery interval, but those with early delivery in our group had late postpartum recovery, indicating that they had severe/complicated preeclampsia that had demanded early termination.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…37 These women should be evaluated with respect to continuing proteinuria, persistent hematuria, or impaired renal function and a percutaneous renal biopsy should be performed in women who have positive signs of underlying renal disease. 30 Limitation of our study-We did not study the diagnosis-todelivery interval, but those with early delivery in our group had late postpartum recovery, indicating that they had severe/complicated preeclampsia that had demanded early termination.…”
Section: Discussionmentioning
confidence: 88%
“…Four patients (29%) were diagnosed with MPGN, four patients (29) were diagnosed with IgA nephropathy (IgAN), one patient (7 %) was diagnosed with FSGS, and one patient (7 %) was diagnosed with amyloidosis. 30 Thus persistent proteinuria in PE women require further investigations and should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the primary underlying problem may lie in the kidneys in a greater proportion of cases with preeclampsia, especially among women who first develop proteinuria. In addition, among 14 patients with preeclamptic Turkish women with persistent proteinuria after delivery, biopsy-proven underlying renal diseases were present in 10 patients: membranoproliferative glomerulonephritis in four (29%), IgA nephropathy in four (29%), FSGS in one and amyloidosis in one in results of a recent study by Unverdi et al [10].…”
Section: Discussionmentioning
confidence: 90%
“…Unverdi et al [10] reported that proteinuria and/or hematuria persisted after 3 months postpartum in 7.3 % (34/463) of women with PE; 14 patients without history of previous glomerulonephritis consented to kidney biopsy, and 29 % (4/14)…”
Section: Discussionmentioning
confidence: 99%